Measurement of hepcidin isoforms in human serum by liquid chromatography with high resolution mass spectrometry. (March 2017) - Handley, Simon; Couchman, Lewis; Sharp, Paul; Macdougall, Iain; Moniz, Cajetan
Aim: Hepcidin-25 is the master regulator of iron homeostasis. N -truncated isoforms of hepcidin-25 have been identified (hepcidin-20, -22, -24), although data on the concentrations of these isoforms are sparse.Materials & methods: Serum was mixed with aqueous formic acid, and the supernatant loaded onto a 96-well-SPE-plate. Eluted analytes were analyzed using LC–HR-MS. Forty-seven paired dipotassium-EDTA human plasma and serum samples were analyzed.Results: The LLOQ was 1 μg/l (all analytes). Accuracy and precision were acceptable. There was a good correlation (R 2 >0.90, all analytes) between matrices. The median (range) serum hepcidin-20, -22, -24 and -25 concentrations measured were 4 (1–40), 8 (2–20), 8 (1–50) and 39 (1–334) μg/l, respectively.Conclusion: LC–HR-MS is widely applicable to the measurement of hepcidin-25, and truncated isoforms.